2017
DOI: 10.1007/s11356-017-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric heavy metal deposition in agro-ecosystems in China

Abstract: Atmospheric deposition has become one of the main sources of heavy metals in crops in developed and industrial zones in China for the past several years. However, lack of data of the agro-ecosystems on the vast areas of China makes it difficult to assess the impacts of air pollution on the heavy metal accumulation in crops. In this study, with deposit samples from 67 sites located at different agro-ecosystems (typical, factory nearby, town nearby, roadside, and remote) of four natural regions [Huanghuai (HH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…To prove the representativeness, we conducted extensive comparisons between measured fluxes in this study and fluxes measured in other areas of China. Results showed that the atmospheric deposition rates around the BS and NYS were lower than those measured in the Pearl River Delta (Wong et al, 2003), North China (Pan and Wang, 2015), Beijing (Guo et al, 2017), and agro-ecosystems in China (Zhang et al, 2017b). However, these deposition rates were comparable with the deposition levels monitored in the Jiaozhou Bay and in several Chinese terrestrial ecosystems (Xing et al, 2017;Zhu et al, 2016).…”
Section: Atmospheric Deposition Ratesmentioning
confidence: 71%
“…To prove the representativeness, we conducted extensive comparisons between measured fluxes in this study and fluxes measured in other areas of China. Results showed that the atmospheric deposition rates around the BS and NYS were lower than those measured in the Pearl River Delta (Wong et al, 2003), North China (Pan and Wang, 2015), Beijing (Guo et al, 2017), and agro-ecosystems in China (Zhang et al, 2017b). However, these deposition rates were comparable with the deposition levels monitored in the Jiaozhou Bay and in several Chinese terrestrial ecosystems (Xing et al, 2017;Zhu et al, 2016).…”
Section: Atmospheric Deposition Ratesmentioning
confidence: 71%
“…Several studies have found that 50%-70% less cadmium accumulates in maize and some vegetables (amaranth, cabbage, and lettuce), most likely due to the supply of calcium from lime and its absorption competition with cadmium [80][81][82] . However, this lime addition might not diminish cadmium uptake in alkaline soils, under deeper rooting or due to the antagonism with Mongolian Plateau, Northwest 1.04 [63] Beijing, North China 4.75 [64] Tianjin, North China 5.30 [64] Hebei, North China 5.57 [64] Henan, North China 4.93 [65] Shanxi, North China 2.04 [65] Fujian, Southeast 0.91 [65] Lianyuan, Southeast 17.00 [66] Shenzhen, Southeast 7.42 [66] Guizhou, Southwest 2.01 [65] Jiaozhou Bay, Central Yellow Sea 1.30 [67] Daya Bay, South China Sea 1.60 [68] East China Sea 1.78 [69] Southern Yellow Sea 1.80 [69] Ca + in the soil solution [26] . When calculating the cadmium outputs from the soil, crop uptake and leaching must be considered (Table 5) [15,44,61] .…”
Section: Cadmium Balance In Arable Soilmentioning
confidence: 99%
“…Ni is considered an indicator of fuel combustion [ 39 , 40 ] and used in industrial production as a raw material or catalyst [ 46 , 50 ]; thus, Ni and TN, TP, and NH 4 + -N lack the same source, although they have significant positive relationships. Pb is not only in the tail gas of oil combustion (entering the lake via atmospheric sedimentation) [ 51 ], but also an important element in automobile manufacturing (such as additives for airbag detonators) [ 52 ]; thus, automobile exhaust and industry are the major sources of Pb. Mn is commonly used as a reducing agent and catalyst in the production of materials such as alloys and magnetic components [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Pb is not only the waste from automobile manufacturing and fuel [ 51 , 52 ], but also an important component of feed additives together with Zn and Cu [ 49 ]. Apart from the production of fertilizer and pesticides (sodium arsenate and calcium arsenate) [ 38 ], As can also be used together with Co, Ni, and Mn in chemical industry and metal smelting as a combustion promoter or catalyst [ 39 , 51 ]. Cd and Zn are indispensable raw materials for brakes, tires, and lubricants [ 54 ].…”
Section: Resultsmentioning
confidence: 99%